Empirical proposal to create a scorecard for SMEs from a strategic interpretation of the International Financial Reporting Standards - García Carvajal, Santiago; Dueñas, Robinson; Acuña Barrantes, Henry (Cooperativismo & Desarrollo, 2017)
Introduction: Nowadays the need to create and design procedures that have as purpose the adequate functioning of the business system in a universal scale arises. These advances include the ifrs, International Financial Reporting Standards, which are the most discussed and which present considerable application cases throughout the whole international business arena. Methodology: A review of the convergence processes of the traditional accounting standards to the ifrs is proposed, so as to interpret the possible consequences that could emerge in all the organizational disciplines inside the company, mounted on the platform of an operational scorecard and corroborated by a correlational statistical analysis done to Colombian smes using spss. Results: To elaborate this study, the ifrs procedures for smes were analyzed, adopting ifrs to prepare financial statements in a scorecard, which is correlational in the implementation of the model for smes. The results were more than probabilistic. Conclusions: ifrs constitute a tool of great utility for any company, the adoption of ifrs implies en accounting change that simplifies criteria.
Keywords: balanced dashboard; emerging markets; international financial reporting standards (ifrs); smes